Socio-Cultural Significance of Medical Reforms (Eurasian Medical Research Periodical, 2023)
This article reveals the need for socio-cultural importance of reforms in the field of medicine. The importance of reforms in the field of medicine has been scientifically studied with the fact that the main criterion is to raise a socially and culturally healthy generation in the society.